2006
DOI: 10.1603/0022-0493-99.6.1979
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sexual Compatibility Between Laboratory and Wild Mexican Fruit Flies Under Laboratory and Field Conditions

Abstract: The sexual compatibility between laboratory (LF) and wild (WF) strains of the Mexican fruit fly, Anastrepha ludens (Loew), was analyzed using analogous methodologies and experimental arenas under both laboratory and field conditions. Sexual compatibility was quantified with the following indices: the isolation index (ISI), male relative performance index (MRP), female relative performance index (FRPI), and the relative sterility index (RSI). ISI detected a certain level of incompatibility between strains under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…Differences in the calling and mating behavior between a laboratory mass‐reared strain and wild males of A. ludens have been reported in a previous study. Those laboratory mass‐reared males started calling earlier and for longer periods and mated earlier than wild males under laboratory conditions (Meza‐Hernández & Díaz‐Fleischer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the calling and mating behavior between a laboratory mass‐reared strain and wild males of A. ludens have been reported in a previous study. Those laboratory mass‐reared males started calling earlier and for longer periods and mated earlier than wild males under laboratory conditions (Meza‐Hernández & Díaz‐Fleischer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Males were identified by marking the individuals 48 h before the tests with a numbered tag adhered to the thorax (Meza-Hernández & Díaz-Fleischer, 2006). In each field cage, 30 Tapachula-7 virgin males (Parental), 30 wild virgin males and 30 wild virgin females, all sexually mature, were released (1:1:1 ratio).…”
Section: Mating Competition and Selectionmentioning
confidence: 99%
“…We choose these two times to compare activity levels as it comprises the sexual activity period, when we would expect both strains to be most active (Aluja et al, 2000). Furthermore, previous studies have found that mass-reared flies are more active at 16:00 h than wild flies (Meza- Hernández & Díaz-Fleischer, 2006). Twenty three males for each treatment type were analyzed.…”
Section: Activity Of Tap-7 Malesmentioning
confidence: 99%